STUDY OF GLUTATHIONE-S-TRANSFERASE GENES POLYMORPHISM BY MULTIPLEXPCR IN PATIENTS WITH CIRRHOSIS ASSOCIATED WITH HEPATITIS C: ONE EGYPTIAN STUDY - NAHLA ANBER,; MAYSAA EL SAYED ZAKI, (International Journal of Pharma and Bio Sciences, 2016)
The pathogenesis of cirrhosis associated with HCV is a multifactor. Among theories of this disorder is host factors associated with genetic polymorphism. Glutathione –s-transferases enzymes appear to have a role in hepatic fibrosis. The aim of the present study is to determine the distribution of GSTM1 gene and GSTT1 gene polymorphisms in some Egyptian patients with chronic hepatitis C associated with cirrhosis compared to healthy control subjects. This study included seventy one patients complaining of advanced liver cirrhosis associated with HCV infection. In addition, one hundred healthy subjects with cross age and sex were included as healthy control. Blood samples were obtained from each subject and subjected to determination of GSTT1 and GSTM1 genotypes polymorphism by multiplex polymerase chain reaction. Patients have more frequent GSTM1 and GSTT1 null genotypes compared to control subjects (29.6% OR 2.20, 95% CI: 1.05- 4.6, P=0.03) and (28.2% OR 0.2, 95%CI: 0.09-0.53, P=0.03); respectively. The distribution of GSTM1 and GSTT1 according to fibrosis score, revealed high significant association (P=0.0001) between GSTM1 null genotype (85%) ,GSTT1 null genotype (85%) and combined GSTM1 &GSTT` null type (85%) with advanced fibrosis. The present study highlights the prevalence of GSTT1 and GSTM1 polymorphisms in some Egyptian patients with hepatic fibrosis on top of HCV infection. Null genotypes for both GSTT1 and GSTM1 are associated with hepatic fibrosis. Combined null polymorphism is a predisposing risk factor beside older age in development of advanced cirrhosis. Genotypic study of GSTT1 and GSTM1 polymorphism could aid in prediction the high risk patients for advanced liver fibrosis associated with HCV.